2021
DOI: 10.1186/s12889-021-11850-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased awareness and knowledge of Lyme Borreliosis and tick bite prevention among the general population in France: 2016 and 2019 health barometer survey

Abstract: Background Lyme borreliosis (LB) is the most frequent tick-borne disease in France. In the absence of a vaccine, LB prevention mainly relies on reducing tick bites. In 2016, the French Ministry of Health launched a national plan against tick-borne infections, including a prevention component. To evaluate the impact of this prevention strategy, we assessed knowledge and practices of tick bite prevention using the 2016 and 2019 national surveys on health attitudes and beliefs known as the French … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
6
10
1
Order By: Relevance
“…Indeed, there are specific HFRS prevention campaigns targeting forestry workers, as it is part of the list of occupational diseases in France [ 38 ]. Moreover, a previous French study indicated that forestry workers had greater knowledge about tick-borne diseases and were more likely to protect themselves than the general French population [ 39 ], indicating that they do follow recommendations and have a better knowledge of occupational diseases than the general population. Since the original study was aimed at investigating the seroprevalence of B. burgdorferi sl, we did not collect information on the use of preventive measures for hantavirus infections (such as the use of masks while working), and we could not evaluate their relationship with hantavirus seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are specific HFRS prevention campaigns targeting forestry workers, as it is part of the list of occupational diseases in France [ 38 ]. Moreover, a previous French study indicated that forestry workers had greater knowledge about tick-borne diseases and were more likely to protect themselves than the general French population [ 39 ], indicating that they do follow recommendations and have a better knowledge of occupational diseases than the general population. Since the original study was aimed at investigating the seroprevalence of B. burgdorferi sl, we did not collect information on the use of preventive measures for hantavirus infections (such as the use of masks while working), and we could not evaluate their relationship with hantavirus seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Age-specific analysis indicated children and older adults are particularly at risk of LB. Hypotheses for this finding include higher exposure to ticks among certain age groups, absence of careful body inspection for ticks after returning from outdoor activities (Septfons et al, 2021 ), and increasing susceptibility to developing LB symptoms with age (Oosting et al, 2016 ). Of interest, hospitalization is particularly frequent in 5–9 years of age compared with primary care incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although Limousin is a rural region characterized by a low population density and is heavily forested, these characteristics are not unique to Limousin. According to a population survey, Limousin had the highest proportion of its population bitten by a tick, in 2016 and 2019, which may indicate a higher density of ticks in this region or a higher proportion of its population may engage in activities placing them at risk of being bitten by ticks ( e.g ., forest activities) (Septfons et al, 2021 ). Data from primary care and hospitalizations were consistent across regions, suggesting the criteria used to extract LB data from the PMSI database, although not disease-specific and highly dependent on coding practice, may correctly capture the relative regional trends in LB cases.…”
Section: Discussionmentioning
confidence: 99%
“…This requires understanding how citizens get access to information, integrate it, and modify their behavior ( 65 , 66 ), such as what has been developed for malaria prevention where for instance, an approach combining mass and interpersonal methods result in the positive improvement of prevention [e.g., ( 67 , 68 )]. Septfons et al ( 69 ) reported a trend toward increased knowledge and awareness of tick bites and LD from 2016 to 2019 in France. Indeed, in 2016 66% of participants had heard about LD.…”
Section: Discussionmentioning
confidence: 99%